2020
DOI: 10.1002/hep.31312
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Molecular Signatures Highlight the Sexual Dimorphism of Nonalcoholic Steatohepatitis (NASH)

Abstract: Background and Aims Nonalcoholic steatohepatitis (NASH) is considered as a pivotal stage in nonalcoholic fatty liver disease (NAFLD) progression, given that it paves the way for severe liver injuries such as fibrosis and cirrhosis. The etiology of human NASH is multifactorial, and identifying reliable molecular players and/or biomarkers has proven difficult. Together with the inappropriate consideration of risk factors revealed by epidemiological studies (altered glucose homeostasis, obesity, ethnicity, sex, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 50 publications
(91 reference statements)
4
36
1
1
Order By: Relevance
“…The vinculin cytoplasmic actin-binding protein is enriched in focal adhesions and adherens junctions to contribute to junction stability [40] and plays a vital role as a regulator of apoptosis [41]. Of note, although "cellular adhesion" represents a broad set of processes rather than a specific biologic pathway, this term was previously reported as a GO term consistently enriched in male NASH patients [42]. Furthermore, Arendt et al identified differentially expressed genes related to cell-cell adhesion (ANXA2 and MAG) between NAFL and NASH patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…The vinculin cytoplasmic actin-binding protein is enriched in focal adhesions and adherens junctions to contribute to junction stability [40] and plays a vital role as a regulator of apoptosis [41]. Of note, although "cellular adhesion" represents a broad set of processes rather than a specific biologic pathway, this term was previously reported as a GO term consistently enriched in male NASH patients [42]. Furthermore, Arendt et al identified differentially expressed genes related to cell-cell adhesion (ANXA2 and MAG) between NAFL and NASH patients [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of NAFLD increases in women after menopause, suggesting a protective role of estrogens [ 8 ]. Sex-specific NASH signatures were recently identified in human liver, suggesting that NASH is a sexually dimorphic disease [ 9 ].…”
Section: Nafldmentioning
confidence: 99%
“…Likewise, a recent study that involved large-scale analysis of transcriptomic profiles from human livers suggested the sexually dimorphic nature of NASH and its link with fibrosis and responses to drugs. 55 Unrevealing the genetic mechanisms that contribute to sex-spe-cific NAFLD risk should be urgently addressed in further candidate gene association or GWAS studies of NAFLD. Elucidating the sexspecific genetic architecture of NAFLD represents an important area for future research.…”
Section: Limitations Of the Systems Biology Ap-proachmentioning
confidence: 99%